2020
DOI: 10.1038/s41598-020-67334-6
|View full text |Cite
|
Sign up to set email alerts
|

Fourier analysis of circumpapillary retinal nerve fiber layer thickness in optical coherence tomography for differentiating myopia and glaucoma

Abstract: Differentiating glaucoma from myopic eye is a challenge to ophthalmologists. We try to develop a new discrete Fourier transform (DFT) model for analyzing optical coherence tomography data for the circumpapillary retinal nerve fiber layer (cpRNFL), and investigate DFT as a new diagnostic tool for glaucomatous myopic eyes. The thicknesses of 12 equidistant cpRNFL points were transformed into 6 signals in the frequency domain, ranging from 1 to 6 Hz. In all 232 eyes, generalized linear model showed that 1 Hz, 2 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Similarly, according to this study, the best parameter of the RNFL thickness group is AvgThic with a largest area under the ROC curve 0.803, cut-off value of 63.9, sensitivity of 67%, and specificity of 83.3%. Hsieh et al [19] reported that the largest area below the ROC curve were with: AvgThic, quadrant I and quadrant S. Singh et al [14] also confirmed that the surface of the ROC curve is the largest for AvgThic and quadrant S parameter (Area = 0.963, Area = 0.943), and a slightly smaller area in the case of quadrant I, but with high values of sensitivity of 89% and specificity of 81%. These results are almost the same as results in our study which has underlined the importance of parameter Avg Thic, S, Smax, I and Iavg for the earliest possible diagnosis of glaucoma.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, according to this study, the best parameter of the RNFL thickness group is AvgThic with a largest area under the ROC curve 0.803, cut-off value of 63.9, sensitivity of 67%, and specificity of 83.3%. Hsieh et al [19] reported that the largest area below the ROC curve were with: AvgThic, quadrant I and quadrant S. Singh et al [14] also confirmed that the surface of the ROC curve is the largest for AvgThic and quadrant S parameter (Area = 0.963, Area = 0.943), and a slightly smaller area in the case of quadrant I, but with high values of sensitivity of 89% and specificity of 81%. These results are almost the same as results in our study which has underlined the importance of parameter Avg Thic, S, Smax, I and Iavg for the earliest possible diagnosis of glaucoma.…”
Section: Discussionmentioning
confidence: 88%
“…(1) AUROC of RNFL (Figure S21–S37, Supplemental Digital Content 7, http://links.lww.com/IJG/A745). We detected 13 studies,14,16,22–24,26–32,34 8 studies 14,22,25–30,32 and 4 studies 23,24,29,31 measuring AUROC of average thickness of RNFL, 4 sectors of RNFL, 12-clock-hour sectors of RNFL, respectively. Pooled AUROC ranged from 0.528 to 0.922 depending on area imaged.…”
Section: Resultsmentioning
confidence: 99%
“…(1) AUROC of RNFL (Figure S21-S37, Supplemental Digital Content 7, http://links.lww.com/IJG/A745). We detected 13 studies, 14,16,[22][23][24][26][27][28][29][30][31][32]34 8 studies 14,22,[25][26][27][28][29][30]32 and 4 studies 23,24,29,31 AUROC in hemisphere. Hence, we did not perform an analysis on it.…”
Section: Thickness Difference (Table 1)mentioning
confidence: 99%
“…While past studies have used spatial, trigonometric and Fourier analysis on OCT data, e.g., (22)(23)(24)(25), our framework, involving directional or circular data, is methodologically quite different from those approaches. While our earlier platform CIFU (14) focuses on the aspects of shapes and curves in OCT NRR data, as in functional data analysis (FDA), it does not explicitly address the directional characteristics of OCT data or angular measurements thereof.…”
Section: Discussionmentioning
confidence: 99%